Hot rain means danger memoir of a Force 136 officer Upper Perak - Dobree, Peter George James (Second world war in Malaya, 2007)
This book. Peter Dpbree tells us his experiences during the second world war when he has was forced to retreat down the Malay Peninsular to Singapore and escaped to Ceylon via Sumatera but came back three years later to fight the enemy who had expelled him with approximately a hundred thirty malay guerillas whom he himself raised and trained in the jungle of Grik. He was the first British force 136 agent and liasoned officer who succeeded in forming a fighting unit among the malay and this was then followed by the formation of other groups in Pahang, Kedah dan Kelantan.